Assessment of drivers of Listeria environmental monitoring programs in small- and medium-sized dairy processing plants - Caroline Motzer; Aljosa Trmcic; Nicole Martin; Martin Wiedmann; Samantha Bolten (JDS Communications)
Small- and medium-sized dairy processing plants (SMDPP) may face unique challenges, such as limited financial resources, when implementing Listeria environmental monitoring programs (EMP). To better understand what drives investment in Listeria EMP, 9 SMDPP, which had previously participated in an ∼1-yr longitudinal study focused on implementing Listeria EMP, completed a questionnaire regarding their EMP-associated costs. This questionnaire was used to obtain each plant's (1) self-reported product value (i.e., estimated total value of finished product [ETVFP] in a plant at any given time) and other EMP-associated costs (e.g., corrective action costs), as well as (2) perceived ability to control pathogens in their processing environment. Additionally, we used a predefined rubric to assess each SMDPP's commitment to their Listeria EMP; these data were used to obtain a “food safety culture score” out of 225 possible points. Overall, a wide range of total EMP investments ($1,186.96–$55,530.58) and food safety culture scores (56 out of 225 to 222 out of 225) were reported across plants. Linear regression analysis identified that predictor variables of plant size, overall environmental Listeria prevalence during the EMP implementation period, ETVFP, and food safety culture score were not significantly associated with the outcome of the total amount of money that plants spent on their Listeria EMP (i.e., their total EMP investment). Although small, our study suggests that SMDPP's financial investments in Listeria EMP may be influenced by other external factors or factors not related to food safety, such as owners' gut feelings, beliefs, and attitudes. To address this, we recommend that food safety training and educational programs for small and medium food businesses include coverage of food safety–related business risks.